(untitled) (Research, Society and Development, 2021)
The general objective of the research is to carry out a literature review on the influence of healthy eating in children with autism spectrum disorder (ASD). The following specific objectives are pointed out: to define and characterize the autism spectrum disorder, to understand the main nutritional problems of children with autism; and highlight the importance of healthy eating in people with autistic disorder. The methodology used in this study consists of a narrative review, carried out through surveys in the following databases: PubMed, SciELO, Academic Google and virtual health library (VHL), published from 2014 to 2021. Foods developed by children with ASD, such as food selectivity, iron deficiency, and food allergy affect adequate nutritional intake, which influences the health, behavior, and clinical presentation of the disorder. It is concluded that a diet without gluten, casein, and lots of sugar, but with the addition of vitamin supplements are very positive ways that help to reduce changes in eating behaviors, as well as a decrease in self-aggressive behavior.